2012
DOI: 10.1111/jfs.12019
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR (mPCR) for the Detection of Salmonella spp. and the Differentiation of the Typhimurium and Enteritidis Serovars in Chicken Meat

Abstract: Salmonella enterica subspecies enterica serovars Enteritidis and Typhimurium are important causes of foodborne illness. Methods for simultaneous detection of these serovars may contribute for the adoption of measures to prevent these diseases. The polymerase chain reaction to detect individually or simultaneously the serovars Enteritidis and Typhimurium in foods have been standardized; however, the majority of assays employ the fliC gene as a target for detection of serovar Typhimurium. The detection of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…PCR assays have been developed for the detection of different gene-encoded virulence factors, viz. simplex PCR for Salmonella enterotoxin (stn) 12 , Salmonella enteritidis fimbriae (sef ) and plasmid encoded fimbriae (pef ) 13 , and multiplex PCR (m-PCR) assays for a combination of a few such virulence factors [14][15][16] . Here, we report the development of a m-PCR for rapid and simultaneous detection of seven major virulence genes of S. enterica.…”
mentioning
confidence: 99%
“…PCR assays have been developed for the detection of different gene-encoded virulence factors, viz. simplex PCR for Salmonella enterotoxin (stn) 12 , Salmonella enteritidis fimbriae (sef ) and plasmid encoded fimbriae (pef ) 13 , and multiplex PCR (m-PCR) assays for a combination of a few such virulence factors [14][15][16] . Here, we report the development of a m-PCR for rapid and simultaneous detection of seven major virulence genes of S. enterica.…”
mentioning
confidence: 99%
“…A recent study from Turkey by Dumen et al (12) also reported SE as the most prevalent (26.6%) serotype both by PCR and by conventional serotyping. In contrast, this serovar was either not detected (7,8) or was detected in very low rates (6) from chicken meat-related or egg samples by conventional or real-time PCR in different studies.…”
Section: Discussionmentioning
confidence: 96%
“…Differences in the detection rate of SE by rPCR in this study compared to the findings of others could mainly be related to the country and prevalence of the serovar in that region during that time period. In addition, sample size and type, and the validity of the PCR detection system (specificity, sensitivity, accuracy/reliability), can be the main factors among others affecting this outcome (7,8,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplex PCR (mPCR) method can be used to detect multiple parasites including different species of hookworm in a single assay ( Verweij et al, 2007;Jonker et al, 2012;Saeki et al, 2013) and reduce detection time, costs and labor that is otherwise associated with running multiple assays (Toplak et al, 2012). However, it should be noted that multiple primers pairs must function under the same reaction conditions and do not form primer dimers during the reaction.…”
Section: Molecular (Pcr/mpcr/qpcr) Methodsmentioning
confidence: 99%